The practice profile of occupational therapists delivering work practice services in South Africa - Ver Loren Van Themaat, Dorita Cornelia (Department of Health and Rehabilitation Sciences, 2015)
Over the last decade, industrialised countries have experienced a significant increase in the cost of sickness, disability and employment injury benefits. Concurrently, an increase has been noticed in the need for work rehabilitation due to reasons such as disability as a result of an aging work-force, and work-related stress. Occupational therapists play a crucial role in providing work practice services, but little is known about the type of services they provide or the settings in which they are offered. The aim of this study was to describe the practice profile of occupational therapists delivering services within the field of work practice in South Africa to determine whether the work-related needs of the South African population are being met and to inform future planning of services. Methods: A descriptive cross-sectional study was undertaken. A self-administered survey was distributed to occupational therapists in the field of work practice within South Africa. Convenience and snowball sampling were used to target as many participants as possible. A survey based on the literature was developed and underwent pilot testing. Content and face validity was determined by a panel of experts who participated in a focus group. Instrument utility was established with occupational therapists who did not work in this field. Frequencies and proportions were determined for categorical data. Chi-square tests of association were undertaken to determine whether there were any significant associations between identified variables. A p-value of < 0.05 was considered significant. Open-ended questions were post coded.